Design of a Spa Resort Micro-Logistical Model - JABLONSKÁ, Jana; MARASOVÁ, Daniela; GRINČOVÁ, Anna; TIMČÁK, Gejza M. (Journal of Environmental Management and Tourism; Vol 7 No 3 (2016): JEMT Volume VII Issue 3(15) Fall 2016, 2016)
The paper presents a novel approach to managing spa resort through micro-logistical model, using strategic planning, including the calculation of population development and of target customer groups using regression analysis. The paper proposes also a marketing plan for a new spa center, using marketing tools as part of the executive plan.
Keywords: logistics; material flow management; spa resort; model